2007
DOI: 10.1097/01.pai.0000213114.27978.3a
|View full text |Cite
|
Sign up to set email alerts
|

Merlin Expression in Secretory Meningiomas: Evidence of an NF2-independent Pathogenesis?

Abstract: One of the most common chromosomal regions implicated in the meningiomas tumorigenesis is 22q12 where the neurofibromatosis 2 (NF2) gene resides. The NF2 tumor-suppressor gene encodes for the merlin/schwannomin protein, which is responsible for the inherited disease neurofibromatosis 2. NF2 gene mutations predominantly occur in transitional and fibroblastic meningiomas, whereas the meningothelial variant is less affected. Secretory meningioma is an infrequent meningioma subtype. Its most typical morphologic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Pavelin et al ( 21 ) identified merlin expression in 72 of 170 (42.4%) meningioma samples: 40% of grade I, 53% of grade II, and 54% of grade III meningiomas. Buccoliero et al ( 12 ), reported merlin expression in 100% of grade I meningiomas examined, which is identical to the present study. We did not identify any statistically significant association between merlin expression and meningioma tumor grade, which is similar to other reports demonstrating no relationship between the expression of merlin and the degree of meningioma.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pavelin et al ( 21 ) identified merlin expression in 72 of 170 (42.4%) meningioma samples: 40% of grade I, 53% of grade II, and 54% of grade III meningiomas. Buccoliero et al ( 12 ), reported merlin expression in 100% of grade I meningiomas examined, which is identical to the present study. We did not identify any statistically significant association between merlin expression and meningioma tumor grade, which is similar to other reports demonstrating no relationship between the expression of merlin and the degree of meningioma.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of signals indicating merlin ( 12 ), NDRG2 ( 13 ), ERBB2 ( 14 ) (weak, moderate or strong) expression in the cytoplasm and c-MYC ( 15 ) (weak or strong) expression in the nucleus or perinucleus were considered positive. Slides were assessed by two independent and blinded observers (B.R.O.…”
Section: Methodsmentioning
confidence: 99%
“…Neurofibromatosis 2-associated meningiomas and about 60% of sporadic meningiomas are caused by mutation and/or deletion of the NF2 gene. 16,17 In our case, with the limitations of the method of study (RT-PCR), we could not substantiate a possible NF2 gene inactivation.…”
Section: Discussionmentioning
confidence: 70%
“…41,65 For instance, 70%-80% of fibroblastic and transitional meningiomas possess the mutation, whereas only 25% of meningoepithelial and 1% of secretory meningiomas have the mutation, possibly suggesting alternative tumorigenesis pathways among these subtypes. 4 Similarly, only 40% of sporadic meningiomas possess the NF-2 mutation. 65 On the other hand, within subtypes in which the mutation does occur, there appears to be no major variation in frequency among the different tumor grades, 3 suggesting that this alteration is more likely to be involved with meningioma initiation rather than malignant transformation.…”
Section: Targeted Molecule Chemotherapeutic Agentsmentioning
confidence: 99%